Public Health Foundations : Concepts and Practices. - Andresen, Elena (John Wiley & Sons, Inc., 2010)
Responding to the growing interest in public health, Public Health Foundations is an accessible and comprehensive text that offers a reader-friendly introduction to core concepts and current practices. The authors use an engaging approach to topics such as epidemiology and pharmacoepidemiology, biostatistics, infectious disease, environmental health, social and behavioral sciences, health services and policy, quantitative and qualitative research methods, and health disparities. Ready for the classroom, each chapter includes learning objectives, an overview, detailed explanations, case studies.